Juridical Analysis of the Distribution of Joint Assets in Divorce According to Indonesian Positive Law - Carissa Patricia Hong; Jelita Safitri Ananda; Muh. Abriel Givari Riser (CV. Rayyan Dwi Bharata, 2023)
In a divorce, there is a process of dividing joint assets. Issues regarding joint assets often occur between ex-husbands and ex-wives. For Muslims, the provision for sharing joint assets is contained in article 97 of the Compilation of Islamic Law (KHI) that